Synergism of antimicrobial and anti-adhesive activity of Nocardia vaccinii IMV B-7405 surfactants in a mixture with essential oils - Pirog, Tatiana; Kliuchka (Nykytyuk), Lilia; Kliuchka, Igor; Shevchuk, Tetiana; Iutynska, Galyna (My University, 2020)
An increase in the antibiotic resistance of pathogenic microorganisms has stimulated the search for alternatives to antibiotics substances of natural origin, which are essential oils (EO) and non-toxic biodegradable microbial surfactants. Aim. To investigate the antimicrobial and anti-adhesive activity of a mixture of EO and surfactants of Nocardia vaccinii IMV B-7405 synthesized on various oil-containing media. Methods. N. vaccinii IMV B-7405 was grown in medium containing as carbon source refined sunflower oil, oil after frying french fried potatoes, potato wedges and meat. The surfactants were extracted from supernatant of cultural liquid by modified Folch mixture. The antimicrobial action of tea tree, cinnamon and lemongrass EO, surfactants and their mixtures was determined by index of the minimum inhibitory concentration (MIC). Synergistic effect of surfactants and EO was evaluated by indicator of fractional inhibitory concentration. The degree of bacteria and fungi biofilms destruction under the action of surfactants, EO and their mixtures was determined by spectrophotometric method. Results. It was found that N. vaccinii IMV B-7405 surfactants synthesized on all oil-containing substrates showed a synergistic antimicrobial and anti-adhesive activity with the investigated EO. MIC of a surfactants and EO mixture against bacteria (Bacillus subtilis BT-2 (spores), Escherichia coli IEM-1, Staphylococcus aureus BMS-1) and yeast (Candida albicans D-6, Candida utilis BVS-65 and Candida tropicalis RE-2) were 2–20 μg/ml and were significantly lower than each compound separately (156–625 and 8–80 μg/ml for EO and surfactants, respectively). The destruction of bacterial and yeast biofilms under the action of a mixture of surfactants (20–40 μg/ml) and EO (20–40 μg/ml) was 1.3–2.9 times higher compared with using of each component separately at similar concentrations. Conclusions. The data presented the possibility of using a mixture of EO and surfactants not only to reduce their MIC, but also as effective antimicrobial and anti-adhesive agents.
Keywords: поверхнево-активні речовини; ефірні олії; синергічна дія; антимікробна активність; руйнування біоплівок; кафедра біотехнології і мікробіології; Nocardia vaccinii IMB В-7405; surfactants; essential oils; synergistic action; antimicrobial activity; destruction of biofilms